The Use of Plickers for Formative Assessment of Vocabulary Mastery - Maya Masita; Nur Fitri (Universitas Cokroaminoto Palopo, 2020)
The use of technology considered has able to help the learning process, especially in teaching English. In the industry revolution 4.0, there are some alternatives to teach English effectively. Plickers is an application that can help the teachers to measure student capability. This application used printable paper clickers to assign each student using the Plickers card. The teacher is instantly checking the student responses and assessment data for every question. This study was using mixed methods design to describe the use of Plickers for formative assessment of vocabulary mastery. The finding shows that Plickers help the teacher in preparing, executing, and examining in formative assessment. This application was able to improve students’ motivation and participation.